Aplikasi Analisis Manajemen Resiko Untuk Membantu Pengambilan Keputusan Menggunakan Metode Decision Table Berbasis Web (Studi Kasus SMKN 1 Jenangan Ponorogo) - Dihin Muriyatmoko; Edi Satriyanto; Eru Puspita (Fountain of Informatics Journal, 2016)
Decision making by considering is very important in an institution. Generally, in choosing a solution of the problem is only take from a meeting, discussion or vote among the leader of each division. But it usually needs more time if the problems are the repetitive and less measurable,  then it takes an application so that decision-making to be effective, efficient, systematic and measurable. This application use decision table method to classifies each risk by considering the scale of likelihood and consequence, then of both these parameters will be taken risk management matrix that will determine the best solution.  This application not absolutely and only help to give the recommendation with the minimum value, so on each solution and risk have a value and the test results of the respondents indicated that the application is able to assist institutions in decision-making as much as 50 percent.